Cutting tool and machining method for titanium alloy material

By adding titanium-based alloy powder to the bonding phase of the titanium alloy cutting tool, combined with modified CeO2 and multi-layer coating technology, the problem of insufficient hardness and toughness of the titanium alloy tool under high temperature and high speed cutting conditions is solved, and the thermal stability and cutting efficiency of the tool are significantly improved.

CN119588936AActive Publication Date: 2025-03-11HEYUAN FUMA CEMENTED CARBIDE CO LTD

Patent Information

Application Number
CN202411905670.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing titanium alloy cutting tools have insufficient hardness, lack of toughness and poor thermal fatigue resistance under high temperature and high-speed cutting conditions, resulting in short tool life and low cutting efficiency.

Method used

A cutting tool processing method for titanium alloy material is adopted. Multi-layer coatings (TiN, CrAlN, CrAlSiN, CrAlBN) are formed by adding titanium-based alloy powder to the bonding phase and combining modified CeO2, ball milling and segmented sintering techniques to form a multi-layer coating (TiN, CrAlN, CrAlSiN, CrAlBN) to improve the hardness, toughness and thermal stability of the tool.

Benefits of technology

It significantly improves the high temperature strength, heat resistance and crack resistance of cutting tools, extends the tool life, improves cutting efficiency, and reduces the friction coefficient and avoids coating peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204321910000151
    Figure BDA0005204321910000151
Patent Text Reader

Abstract

The invention discloses a titanium alloy material cutting tool and a machining method, and the machining method comprises the following steps: proportioning a hard phase WC, a binding phase and an additive according to a ratio, carrying out ball milling, spray drying and compression molding to obtain a tool blank, carrying out segmented sintering treatment, machining and molding to obtain the cutting tool, and then carrying out heat treatment to obtain the titanium alloy material cutting tool. Sequentially carrying out electromagnetic coupling strengthening treatment and surface coating plating treatment to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer; the titanium-based alloy powder is added into the binding phase, so that the high-temperature strength, the heat resistance and the lightweight characteristic of the cutting tool can be enhanced; the modified CeO2 can improve the microstructure uniformity, the interface bonding force and the oxidation resistance of the cutter, so that the density and the crack resistance are improved; electromagnetic coupling strengthening treatment and multi-layer coating deposition treatment are carried out on the cutting tool, the hardness, wear resistance, oxidation resistance and high temperature resistance of the surface of the tool can be remarkably improved, and meanwhile coating stripping is effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium alloy cutting tools, and in particular to a titanium alloy cutting tool and a processing method. Background Art

[0002] In the field of mechanical processing, cutting tools are key tools in the processing technology, and their performance directly affects the processing accuracy, efficiency and surface quality of the workpiece. With the widespread application of high-strength materials and difficult-to-process alloys in aerospace, automobile manufacturing and other fields, traditional cutting tool materials have gradually exposed the problems of insufficient hardness, lack of toughness and poor thermal fatigue resistance under high temperature and high-speed cutting conditions, resulting in short tool life and low cutting efficiency, which is difficult to meet the needs of modern industry for efficient and precise processing. In order to solve these problems, the improvement of tool materials has become a key research direction. Among them, by introducing lightweight and high-strength materials such as titanium alloys into the tool matrix, combined with its excellent specific strength and heat resistance, the comprehensive mechanical properties of the tool can be effectively improved. However, the introduction of titanium alloys also faces a series of technical bottlenecks, such as its insufficient bonding force with the hard phase and the bonding phase, which will cause the problem of uneven microstructure of the tool matrix and reduced strength; in addition, the existing technology lacks effective solutions in the synergistic optimization of titanium alloys and other functional additives, making it difficult to comprehensively improve the hardness, toughness and processing thermal stability of the tool.

[0003] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a cutting tool and a processing method for titanium alloy material which can improve the hardness and toughness of the cutting tool and improve the thermal stability of the product.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] A method for machining a titanium alloy cutting tool comprises the following steps:

[0007] S1. Prepare the raw materials according to the following weight percentages:

[0008] Hard phase WC75%-80%;

[0009] The bonding phase is composed of metal cobalt and titanium-based alloy powder, 10%-15%, wherein metal cobalt accounts for 50%-60% of the total bonding phase, and the titanium-based alloy powder accounts for 40%-50%. The chemical composition of the titanium-based alloy powder is: titanium 68%-75%, aluminum 15%-25%, and vanadium 4%-8%;

[0010] Additive 5%-8%, the additive consists of the following ingredients: TiO 2 2%-3%, TiB2 1%-2%, and modified CeO 2 2%-3%;

[0011] S2, putting the hard phase, the binder phase and the additive into a ball mill according to the raw material ratio for ball milling, and obtaining a mixed powder after spray drying;

[0012] S3, pressing the mixed powder into a shape to obtain a tool blank;

[0013] S4, sintering the tool blank by a segmented sintering method;

[0014] S5, mechanically cutting the sintered tool blank to obtain a cutting tool;

[0015] S6. Perform electromagnetic coupling strengthening treatment and surface coating treatment on the cutting tool in sequence to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer on the surface of the cutting tool in sequence.

[0016] Using the above technical solution, in step S6, the specific process of electromagnetic coupling enhancement processing is as follows:

[0017] After the cutting tool is ultrasonically cleaned, it is loaded into the electromagnetic coupling processing equipment, the electromagnetic field frequency is set to 2MHz, the magnetic field strength is set to 150mT, and then high-purity nitrogen is introduced. The gas flow rate is controlled at 60-80L / min, and then the temperature is gradually increased to 600-800℃ at a heating rate of 10-15℃ / min, thereby decomposing the nitrogen into high-energy active nitrogen ions and forming a TiN layer on the surface of the cutting tool.

[0018] Using the above technical solutions, in step S6, the specific process of surface coating treatment is as follows:

[0019] In an Ar atmosphere, the cutting tool is subjected to ion bombardment treatment with a substrate bias voltage of -180V for 10-20min, and then high-purity Ar is introduced with a flow rate controlled at 40-50sccm, and a substrate bias voltage of -170V is applied. The Cr and Al targets are started with sputtering powers of 140W and 130W, respectively, and the deposition time is 60min to obtain a CrAlN layer.

[0020] Add high purity N 2 , Ar and N 2 The flow rates are 40sccm and 10sccm respectively, and the target material is adjusted to Cr 0.35 Al 0.45 Si 0.10 The alloy target material, the sputtering power is 150W, the substrate bias voltage is -100V, and the deposition time is 30min to obtain the CrAlSiN layer;

[0021] Then in Ar and N 2 High purity B is introduced into the atmosphere 2 H 6 , gas flow rate is 10-20sccm, target material is Cr 0.30 Al 0.60 B 0.10 , the sputtering power is 150 W, the substrate bias is -100 V, and the deposition time is 30 min to obtain the CrAlBN layer.

[0022] By adopting the above-mentioned technical solutions, the modified CeO 2 The modification process is:

[0023] CeO with a particle size of 100-200 nm 2 The particles were placed in an ultrasonic cleaning device and a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1 was added for 10-15 minutes. Then, the particles were filtered with filter paper to remove the CeO 2 particles, and then CeO 2 The particles were placed in an oven at 60-80°C and dried for 3-5 hours to ensure that CeO 2 There is no residual liquid on the particle surface;

[0024] Then CeO 2 The particles were placed in a vacuum plasma treatment device, and the chamber of the vacuum plasma treatment device was evacuated to a vacuum degree below 0.001 Pa. Then, high-purity Ar was introduced into the chamber to maintain the pressure in the chamber at 20-50 Pa. The radio frequency plasma source was started with a frequency of 13.56 MHz and a power of 200-400 W to make CeO 2 The particles are evenly bombarded in the plasma environment, and the treatment time is 3-5 minutes.

[0025] By adopting the above technical solutions, the thickness of the TiN layer is 1-4 μm.

[0026] By adopting the above-mentioned technical solutions, the thickness of the CrAlN layer is 0.5-0.7 μm, the thickness of the CrAlSiN layer is 0.6-0.8 μm, and the thickness of the CrAlBN layer is 0.7-0.9 μm.

[0027] Using the above technical solutions, in step S2, ethanol is added as a ball milling medium during the ball milling of the raw materials, and 0.5wt% of polyethylene glycol is added as a molding agent for ball milling, the ball-to-powder ratio is 10:1, and the ball milling time is 12-24h.

[0028] Using the above-mentioned technical solutions, in step S3, the mixed powder is first preliminarily pressed by cold isostatic pressing equipment at a pressing pressure of 200-300 MPa, and then the preliminarily pressed tool blank is placed in a hot isostatic pressing equipment for high-temperature compaction treatment, with the temperature controlled at 900-1100°C, the pressure at 50-100 MPa, and the insulation time at 1-2 hours.

[0029] Using the above technical solutions, in step S4, the segmented sintering method is specifically as follows:

[0030] S41, dewaxing stage: after evacuating the sintering furnace to 20-50Pa, hydrogen is introduced, and the furnace temperature is increased to 350-400°C at a heating rate of 35-45°C / min, and kept at this temperature for 4-6h;

[0031] S42, vacuum sintering stage: the furnace temperature is raised to 1250°C at a heating rate of 20-25°C / min, and kept at this temperature for 50-60min, and then the furnace temperature is raised to 1350°C at a heating rate of 8-10°C / min, and kept at this temperature for 70-90min;

[0032] S43, pressure sintering stage: after vacuum sintering is completed, argon gas is introduced into the furnace to increase the pressure in the furnace to 50-100 mbar, and at the same time, the furnace temperature is increased to 1450-1500°C at a heating rate of 5°C / min and maintained for 30-60 minutes;

[0033] S44, cooling stage: after stopping heating, the furnace temperature is lowered to 1000°C at a cooling rate of 12-25°C / min, 950-980mbar argon is introduced at this temperature for forced cooling, and the cooling rate is controlled at 10-15°C / min until the furnace temperature is lower than 100°C, and the tool blank is taken out.

[0034] The technical solution also provides a cutting tool for titanium alloy material, which is prepared by using any of the above-mentioned cutting tool processing methods for titanium alloy material.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention can enhance the high temperature strength and heat resistance of the cutting tool by adding titanium-based alloy powder to the binder phase, avoid the problem of softening and failure of the binder phase during high temperature cutting, and at the same time give the tool lightweight and high strength characteristics, thereby improving cutting efficiency; secondly, adding modified CeO 2 The uniformity of the microstructure and the interface bonding strength of the material are improved, thereby improving the densification effect of sintering, making the tool free of stress concentration points, and significantly enhancing the crack resistance. In addition, CeO 2The antioxidant effect can improve the wear resistance and service life of the tool; the introduction of the pressure sintering stage in the sintering process can effectively eliminate the micropores inside the material, significantly improve the density, mechanical strength and toughness of the material, optimize the microstructure, and make the tool show better heat resistance and fatigue resistance in high-temperature cutting; the electromagnetic coupling strengthening treatment can generate a dense TiN layer on the tool surface, greatly improving the surface hardness and wear resistance of the tool, while enhancing the antioxidant performance, resisting thermal fatigue and oxidative wear in high-temperature cutting; the multi-layer coating treatment deposits CrAlN, CrAlSiN and CrAlBN coatings layer by layer to form a gradient-optimized structure, taking into account hardness, wear resistance, toughness and high-temperature resistance, which not only reduces the friction coefficient, but also significantly improves the bonding strength between the coating and the substrate, avoiding the problem of coating peeling. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0038] The present invention provides a cutting tool processing method for titanium alloy material, comprising the following steps:

[0039] S1. Prepare the raw materials according to the following weight percentages:

[0040] Hard phase WC75%-80%; The hard phase WC accounts for 75%-80%, which is the strengthening phase of the cutting tool. Its high hardness and wear resistance can effectively resist the strong friction and wear force generated during the cutting process.

[0041] The bonding phase is composed of metal cobalt and titanium-based alloy powder, 10%-15%, wherein metal cobalt accounts for 50%-60% of the total bonding phase, titanium-based alloy powder accounts for 40%-50%, and the chemical composition of titanium-based alloy powder is: titanium 68%-75%, aluminum 15%-25%, vanadium 4%-8%; the bonding phase is composed of metal cobalt and titanium-based alloy powder, wherein the proportion of metal cobalt is 50%-60%, which can ensure good wettability and overall toughness of the material, and the titanium-based alloy powder can improve the high-temperature stability of the cutting tool with its excellent specific strength and heat resistance; the titanium content in the titanium-based alloy is 68%-75%, which can provide the matrix with light and high-strength characteristics, aluminum 15%-25% can improve the alloy's oxidation resistance and high-temperature resistance, and vanadium 4%-8% can refine the grain structure, thereby improving the material's comprehensive mechanical properties;

[0042] Additive 5%-8%, the additive consists of the following ingredients: TiO 2 2%-3%, TiB 2 1%-2%, and modified CeO 2 2%-3%; TiO 2 Provides good wear resistance and thermal stability, TiB 2 Due to its extremely high hardness and corrosion resistance, it can enhance the fatigue resistance of the tool. 2 After plasma modification, its surface activity can be greatly improved, enabling it to better combine with other components, thereby improving the microstructural uniformity and high-temperature performance of the material.

[0043] S2. Put the hard phase, binder phase and additives into a ball mill according to the raw material ratio for ball milling, and obtain mixed powder after spray drying; the ball milling process can fully mix the hard phase WC and the binder phase metal powder through the action of mechanical energy, so that a uniform contact interface is formed between different components, avoiding the local enrichment of a single component, and ensuring the densification and uniformity of the material during sintering.

[0044] S3, pressing the mixed powder into a shape to obtain a tool blank;

[0045] S4, sintering the tool blank by a segmented sintering method;

[0046] S5, mechanically cutting the sintered tool blank to obtain a cutting tool;

[0047] S6. Perform electromagnetic coupling strengthening treatment and surface coating treatment on the cutting tool in sequence to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer on the surface of the cutting tool in sequence. Electromagnetic coupling strengthening treatment can use high-frequency electromagnetic fields to introduce active nitrogen ions on the surface of the cutting tool to form a dense TiN layer, which not only improves the hardness and wear resistance of the cutting tool surface, but also significantly enhances its antioxidant properties, especially in high-temperature cutting environments, it can effectively resist thermal fatigue and oxidative wear; and the subsequent multi-layer coating treatment can further improve the comprehensive performance of the cutting tool by depositing CrAlN, CrAlSiN and CrAlBN coatings layer by layer; specifically, the CrAlN layer has excellent wear resistance and high-temperature oxidation resistance, which can provide basic protection for the tool; the CrAlSiN layer can form a dense nano-composite structure by adding Si elements, which greatly improves the hardness and heat resistance of the coating; the CrAlBN layer can provide additional impact resistance and lubrication properties due to its boron content, thereby reducing the friction coefficient during cutting. In this way, this layer-by-layer deposition structure not only solves the brittleness problem of a single coating, but also improves the bonding strength between the coating and the substrate through the gradient transition between coatings to avoid coating peeling.

[0048] Furthermore, in step S6, the specific process of electromagnetic coupling strengthening treatment is: after the cutting tool is ultrasonically cleaned, it is loaded into the electromagnetic coupling processing equipment, the electromagnetic field frequency is set to 2MHz, the magnetic field strength is set to 150mT, and then high-purity nitrogen is introduced, and the gas flow rate is controlled at 60-80L / min, and then the temperature is gradually increased to 600-800℃ at a heating rate of 10-15℃ / min, thereby decomposing the nitrogen into high-energy active nitrogen ions and forming a TiN layer on the surface of the cutting tool. The cutting tool is placed in an electromagnetic coupling processing device, and the electromagnetic field frequency is set to 2MHz and the magnetic field strength is set to 150mT. In this way, a high-energy electromagnetic field can be excited to decompose nitrogen into high-energy active nitrogen ions. The nitrogen flow rate is controlled at 60-80L / min to ensure the stability of the atmosphere and maintain a uniform distribution of ion concentration to avoid the problem of uneven ion implantation. Subsequently, the temperature is gradually increased to 600-800℃ at a heating rate of 10-15℃ / min. Within this temperature range, the atoms on the surface of the cutting tool substrate have sufficient energy to react chemically with nitrogen ions, thereby forming a dense TiN coating. The TiN layer can not only significantly improve the hardness of the cutting tool surface, but also enhance its antioxidant ability and high temperature resistance, meeting the performance requirements of the cutting tool under extreme cutting conditions.

[0049] Further, in step S6, the specific process of the surface coating treatment is as follows: in an Ar atmosphere, the cutting tool is subjected to ion bombardment treatment under the condition of a substrate bias voltage of -180V, and the bombardment time is 10-20min, and then high-purity Ar is introduced, the flow rate is controlled at 40-50sccm, and a substrate bias voltage of -170V is applied, the Cr and Al targets are started, the sputtering powers are 140W and 130W respectively, and the deposition time is 60min, so as to obtain a CrAlN layer;

[0050] Add high purity N 2 , Ar and N 2 The flow rates are 40sccm and 10sccm respectively, and the target material is adjusted to Cr 0.35 Al 0.45 Si 0.10 The alloy target material, the sputtering power is 150W, the substrate bias voltage is -100V, and the deposition time is 30min to obtain the CrAlSiN layer;

[0051] Then in Ar and N 2 High purity B is introduced into the atmosphere 2 H 6 , gas flow rate is 10-20sccm, target material is Cr 0.30 Al 0.6 B 0.10 , the sputtering power is 150 W, the substrate bias is -100 V, and the deposition time is 30 min to obtain the CrAlBN layer.

[0052] First, a bias of -180V is applied to the substrate in an Ar atmosphere and ion bombardment is performed to remove residual impurities and oxide layers on the tool surface, while inducing atomic rearrangement on the substrate surface and enhancing the bonding force between the coating and the substrate. Subsequently, by adjusting the high-purity Ar gas flow rate to 40-50sccm, a substrate bias of -170V is applied, and sputtering deposition of Cr and Al targets is started, forming a dense CrAlN layer under sputtering powers of 140W and 130W. The coating is mainly a chemical combination of Cr and Al, and its high-temperature oxidation resistance and wear resistance can provide basic protection for the tool. Next, when depositing the second layer of coating, high-purity N is added to the Ar gas. 2 And adjust the target material to Cr 0.35 Al 0.45 Si 0.10 alloy target, applying a substrate bias of -100V to introduce Si into the coating, and using the nanocomposite structure formed by it to improve the hardness and wear resistance of the coating, while enhancing its high temperature stability; when depositing the third layer, by introducing high-purity B 2 H 6 and using Cr 0.30 Al 0.60 B 0.10The target material forms a CrAlBN layer under the conditions of sputtering power of 150W and substrate bias of -100V. Due to the lubricating properties and impact resistance of boron, this layer can reduce the cutting friction coefficient and improve the toughness and thermal fatigue resistance of the tool. This layer-by-layer deposition method achieves a balance of hardness, wear resistance, toughness and bonding strength through gradient optimization of coating composition, effectively enhancing the comprehensive performance of cutting tools in complex cutting environments.

[0053] Furthermore, the modified CeO 2 The modification process is as follows: CeO with a particle size of 100-200nm 2 The particles were placed in an ultrasonic cleaning device and a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1 was added for 10-15 minutes. Then, the particles were filtered with filter paper to remove the CeO 2 particles, and then CeO 2 The particles were placed in an oven at 60-80°C and dried for 3-5 hours to ensure that CeO 2 There is no residual liquid on the particle surface, and then CeO 2 The particles were placed in a vacuum plasma treatment device, and the chamber of the vacuum plasma treatment device was evacuated to a vacuum degree below 0.001 Pa. Then, high-purity Ar was introduced into the chamber to maintain the pressure in the chamber at 20-50 Pa. The radio frequency plasma source was started with a frequency of 13.56 MHz and a power of 200-400 W to make CeO 2 The particles are uniformly bombarded in a plasma environment for 3-5 minutes. Ar ions are excited by a radio frequency plasma source at a frequency of 13.56 MHz and a power of 200-400 W. These high-energy ions react with CeO 2 The interaction between the particle surfaces can break the chemical bonds on the particle surfaces, remove the surface inert layer, and introduce active sites, thereby improving the chemical reactivity and dispersibility of the particles. The treatment time is controlled at 3-5 minutes in order to achieve uniform modification of the particle surface while avoiding changes in particle size and morphology caused by excessive bombardment.

[0054] Furthermore, the thickness of the TiN layer is 1-4 μm.

[0055] Furthermore, the thickness of the CrAlN layer is 0.5-0.7 μm, the thickness of the CrAlSiN layer is 0.6-0.8 μm, and the thickness of the CrAlBN layer is 0.7-0.9 μm.

[0056] Furthermore, in step S2, ethanol is added as a ball milling medium during the ball milling of the raw material, and 0.5wt% of polyethylene glycol is added as a molding agent for ball milling, the ball-to-powder ratio is 10:1, and the ball milling time is 12-24h. Ethanol as a ball milling medium can reduce friction and adhesion during the ball milling process through its liquid properties, effectively reduce the risk of agglomeration between particles, and its volatility can be quickly removed after spray drying without residual impurities; the addition of polyethylene glycol can improve the lubricity and adhesion of the particles to form a more uniform particle distribution during the ball milling process, and act as a binder to enhance the fluidity and pressing performance of the powder in the subsequent molding process; the ball-to-powder ratio is set to 10:1, which can provide sufficient grinding energy while avoiding excessive particle crushing or decreased ball milling efficiency due to an excessively high ratio.

[0057] Furthermore, in step S3, the mixed powder is first preliminarily pressed by cold isostatic pressing equipment at a pressing pressure of 200-300 MPa, and then the preliminarily pressed tool blank is placed in a hot isostatic pressing equipment for high-temperature compaction treatment, with the temperature controlled at 900-1100°C, the pressure at 50-100 MPa, and the insulation time at 1-2 h. Cold isostatic pressing applies a pressure of 200-300MPa to the mixed powder, so that it forms a preliminary densified body in a low temperature environment, ensuring the initial contact and bonding between the particles while maintaining the uniformity of the overall shape; through cold isostatic pressing, the large pores between the powders can be reduced without introducing high temperature stress, and a more stable structural foundation can be provided for subsequent high temperature treatment; then in the hot isostatic pressing stage, the temperature is controlled at 900-1100℃, the pressure is 50-100MPa, and the heat is maintained for 1-2h. The recrystallization of the powder and the complete densification between the particles can be achieved under the combined action of high temperature and high pressure. High temperature can promote atomic diffusion and interface reaction on the surface of the particles, thereby enhancing the bonding force between the particles, while eliminating residual micropores and improving the mechanical properties of the material.

[0058] Furthermore, in step S4, the method of segmented sintering is specifically as follows:

[0059] S41, dewaxing stage: after evacuating the sintering furnace to 20-50Pa, hydrogen is introduced, and the furnace temperature is increased to 350-400°C at a heating rate of 35-45°C / min, and kept at this temperature for 4-6h;

[0060] S42, vacuum sintering stage: the furnace temperature is raised to 1250°C at a heating rate of 20-25°C / min, and kept at this temperature for 50-60min, and then the furnace temperature is raised to 1350°C at a heating rate of 8-10°C / min, and kept at this temperature for 70-90min;

[0061] S43, pressure sintering stage: after vacuum sintering is completed, argon gas is introduced into the furnace to increase the pressure in the furnace to 50-100 mbar, and at the same time, the furnace temperature is increased to 1450-1500°C at a heating rate of 5°C / min and maintained for 30-60 minutes;

[0062] S44, cooling stage: after stopping heating, the furnace temperature is lowered to 1000°C at a cooling rate of 12-25°C / min, 950-980mbar argon is introduced at this temperature for forced cooling, and the cooling rate is controlled at 10-15°C / min until the furnace temperature is lower than 100°C, and the tool blank is taken out. In the dewaxing stage, the sintering furnace is evacuated to 20-50Pa and hydrogen is introduced to ensure the complete decomposition and volatilization of the organic forming agent in a low-oxygen environment, avoiding the formation of pores or carbides due to residual organic matter in the subsequent high-temperature stage; the heating rate of 35-45℃ / min ensures that the dewaxing process is stable and does not introduce excessive thermal stress. Keeping warm for 4-6h can ensure the complete decomposition of the wax. The initial heating of the vacuum sintering stage is 20-25℃ / min to 1250℃ and kept at this temperature for 50-60min, which can promote atomic diffusion and initial bonding on the particle surface, thereby forming a uniform matrix microstructure; then slowly heating to 1350℃ at 8-10℃ / min and keeping warm for 70-90min, which can achieve further diffusion bonding and densification between particles, while inhibiting particle coarsening and stress concentration in the material; the pressure sintering stage In the first stage, argon is introduced and the pressure in the furnace is increased to 50-100mbar. Combined with the heating rate of 5℃ / min, it is increased to 1450-1500℃. The synergistic effect of high temperature and high pressure can be used to compact the material, thereby eliminating residual pores and forming a high-strength dense structure. The setting of the cooling stage can avoid the generation of thermal stress cracks while stabilizing the microstructure. The temperature is gradually reduced to 1000℃ at a cooling rate of 12-25℃ / min, and forced cooling is carried out under the protection of 950-980mbar argon to ensure structural stability and dimensional accuracy. Finally, the temperature is cooled to room temperature at a cooling rate of 10-15℃ / min to avoid thermal stress accumulation or micro defects caused by too fast cooling. The entire segmented sintering process is controlled by precise parameters to ensure that the material has a dense microstructure and excellent performance, which can meet the use requirements of high-performance tools.

[0063] Example 1

[0064] Embodiment 1 of the present invention provides a method for machining a titanium alloy cutting tool, comprising the following steps:

[0065] S1. Prepare the raw materials according to the following weight percentages:

[0066] Hard phase WC80%;

[0067] The binder phase is composed of metal cobalt and titanium-based alloy powder, 15%, wherein metal cobalt accounts for 60% of the total binder phase, and the titanium-based alloy powder accounts for 40%, and the chemical composition of the titanium-based alloy powder is: titanium 75%, aluminum 20%, and vanadium 5%;

[0068] Additive 5%, the additive consists of the following ingredients: TiO 2 2%, TiB 2 1%, modified CeO 2 2%;

[0069] Wherein, the modified CeO 2 The modification process is:

[0070] CeO with a particle size of 200 nm 2 The particles were placed in an ultrasonic cleaning device and a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1 was added for 15 min. Then, the particles were filtered with filter paper to remove the CeO 2 particles, and then CeO 2 The particles were placed in an oven at 80°C and dried for 5 h to ensure that CeO 2 There is no residual liquid on the particle surface;

[0071] Then CeO 2 The particles were placed in a vacuum plasma treatment device, and the chamber of the vacuum plasma treatment device was evacuated to a vacuum degree below 0.001 Pa. Then, high-purity Ar was introduced into the chamber to maintain the pressure in the chamber at 50 Pa. The radio frequency plasma source was started with a frequency of 13.56 MHz and a power of 400 W to make CeO 2 The particles were uniformly bombarded in the plasma environment and the treatment time was 5 min.

[0072] S2, putting the hard phase, the binder phase and the additive into a ball mill according to the raw material ratio for ball milling, adding ethanol as a ball milling medium during the ball milling of the raw materials, and then adding 0.5wt% of polyethylene glycol as a molding agent for ball milling, the ball-to-powder ratio is 10:1, the ball milling time is 24h, and the mixed powder is obtained after spray drying;

[0073] S3, pressing the mixed powder into a tool blank, specifically: firstly using a cold isostatic pressing device to preliminarily press the mixed powder at a pressing pressure of 300 MPa, then placing the preliminarily pressed tool blank into a hot isostatic pressing device for high-temperature compaction treatment, with the temperature controlled at 9000°C, the pressure at 100 MPa, and the holding time at a temperature of 2 h;

[0074] S4, sintering the tool blank by a segmented sintering method, wherein the segmented sintering method is specifically as follows:

[0075] S41, dewaxing stage: after evacuating the sintering furnace to 50Pa, hydrogen is introduced, and the furnace temperature is increased to 400°C at a heating rate of 45°C / min, and kept at this temperature for 6h;

[0076] S42, vacuum sintering stage: the furnace temperature is raised to 1250°C at a heating rate of 25°C / min, and kept at that temperature for 60 minutes, and then the furnace temperature is raised to 1350°C at a heating rate of 10°C / min, and kept at that temperature for 90 minutes;

[0077] S43, pressure sintering stage: after vacuum sintering is completed, argon gas is introduced into the furnace to increase the pressure in the furnace to 100 mbar, and at the same time, the furnace temperature is increased to 1500°C at a heating rate of 5°C / min and maintained for 60 minutes;

[0078] S44, cooling stage: after stopping heating, the furnace temperature is lowered to 1000°C at a cooling rate of 25°C / min, 980mbar argon is introduced at this temperature for forced cooling, and the cooling rate is controlled at 15°C / min until the furnace temperature is lower than 100°C, and the tool blank is taken out;

[0079] S5, mechanically cutting the sintered tool blank to obtain a cutting tool;

[0080] S6, performing electromagnetic coupling strengthening treatment and surface coating treatment on the cutting tool in sequence, so as to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer on the surface of the cutting tool in sequence;

[0081] The thickness of the TiN layer is 1 μm, the thickness of the CrAlN layer is 0.5 μm, the thickness of the CrAlSiN layer is 0.6 μm, and the thickness of the CrAlBN layer is 0.7 μm;

[0082] Among them, the specific process of electromagnetic coupling enhancement treatment is:

[0083] After the cutting tool is cleaned by ultrasonic wave, it is loaded into the electromagnetic coupling treatment equipment, and the electromagnetic field frequency is set to 2MHz, and the magnetic field strength is set to 150mT. Then, high-purity nitrogen is introduced, and the gas flow rate is controlled at 60L / min. Then, the temperature is gradually increased to 800℃ at a heating rate of 15℃ / min, so that the nitrogen is decomposed into high-energy active nitrogen ions and a TiN layer is formed on the surface of the cutting tool;

[0084] The specific process of surface coating treatment is:

[0085] In an Ar atmosphere, the cutting tool was subjected to ion bombardment treatment with a substrate bias of -180 V for 20 min, and then high-purity Ar was introduced with a flow rate of 50 sccm and a substrate bias of -170 V. The Cr and Al targets were started with sputtering powers of 140 W and 130 W, respectively, and the deposition time was 60 min to obtain a CrAlN layer.

[0086] Add high purity N 2 , Ar and N 2 The flow rates are 40sccm and 10sccm respectively, and the target material is adjusted to Cr 0.35 Al 0.45 Si 0.10 The alloy target material, the sputtering power is 150W, the substrate bias voltage is -100V, and the deposition time is 30min to obtain the CrAlSiN layer;

[0087] Then in Ar and N 2 High purity B is introduced into the atmosphere 2 H 6 , gas flow rate is 20sccm, target material is Cr 0.30 Al 0.60 B 0.10 , the sputtering power is 150 W, the substrate bias is -100 V, and the deposition time is 30 min to obtain the CrAlBN layer.

[0088] Example 2

[0089] Embodiment 2 of the present invention provides a method for machining a titanium alloy cutting tool, comprising the following steps:

[0090] S1. Prepare the raw materials according to the following weight percentages:

[0091] Hard phase WC77%;

[0092] The binder phase is composed of metal cobalt and titanium-based alloy powder, 15%, wherein metal cobalt accounts for 50% of the total binder phase, and titanium-based alloy powder accounts for 50%, and the chemical composition of the titanium-based alloy powder is: titanium 68%, aluminum 25%, and vanadium 7%;

[0093] Additive 8%, the additive consists of the following ingredients: TiO 2 3%, TiB 2 2%, and modified CeO3%;

[0094] Wherein, the modified CeO 2 The modification process is:

[0095] CeO with a particle size of 100 2The particles were placed in an ultrasonic cleaning device and a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1 was added for 15 min. Then, the particles were filtered with filter paper to remove the CeO 2 particles, and then CeO 2 The particles were placed in an oven at 60°C and dried for 3 h to ensure that CeO 2 There is no residual liquid on the particle surface;

[0096] Then CeO 2 The particles were placed in a vacuum plasma treatment device, and the chamber of the vacuum plasma treatment device was evacuated to a vacuum degree below 0.001 Pa. Then, high-purity Ar was introduced into the chamber to maintain the pressure in the chamber at 20 Pa. The radio frequency plasma source was started with a frequency of 13.56 MHz and a power of 200 W to make CeO 2 The particles were uniformly bombarded in the plasma environment and the treatment time was 3 min.

[0097] S2, putting the hard phase, the binder phase and the additive into a ball mill according to the raw material ratio for ball milling, adding ethanol as a ball milling medium during the ball milling of the raw materials, and then adding 0.5wt% of polyethylene glycol as a molding agent for ball milling, the ball-to-powder ratio is 10:1, the ball milling time is 12h, and the mixed powder is obtained after spray drying;

[0098] S3, pressing the mixed powder into a tool blank, specifically: firstly using a cold isostatic pressing device to preliminarily press the mixed powder at a pressing pressure of 200 MPa, then placing the preliminarily pressed tool blank into a hot isostatic pressing device for high-temperature compaction treatment, with the temperature controlled at 1100° C., the pressure at 100 MPa, and the holding time at a temperature of 2 h;

[0099] S4, sintering the tool blank by a segmented sintering method, wherein the segmented sintering method is specifically as follows:

[0100] S41, dewaxing stage: after the sintering furnace is evacuated to 20Pa, hydrogen is introduced, and the furnace temperature is increased to 350°C at a heating rate of 35°C / min and kept at this temperature for 4h;

[0101] S42, vacuum sintering stage: the furnace temperature is raised to 1250°C at a heating rate of 20°C / min, and kept at that temperature for 50 minutes, and then the furnace temperature is raised to 1350°C at a heating rate of 8°C / min, and kept at that temperature for 70 minutes;

[0102] S43, pressure sintering stage: after vacuum sintering is completed, argon gas is introduced into the furnace to increase the pressure in the furnace to 50 mbar, and at the same time, the furnace temperature is increased to 1450°C at a heating rate of 5°C / min and maintained for 30 minutes;

[0103] S44, cooling stage: after stopping heating, the furnace temperature is lowered to 1000°C at a cooling rate of 12°C / min, 950mbar argon is introduced at this temperature for forced cooling, and the cooling rate is controlled at 10°C / min until the furnace temperature is lower than 100°C, and the tool blank is taken out;

[0104] S5, mechanically cutting the sintered tool blank to obtain a cutting tool;

[0105] S6, performing electromagnetic coupling strengthening treatment and surface coating treatment on the cutting tool in sequence, so as to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer on the surface of the cutting tool in sequence;

[0106] The thickness of the TiN layer is 4 μm, the thickness of the CrAlN layer is 0.7 μm, the thickness of the CrAlSiN layer is 0.8 μm, and the thickness of the CrAlBN layer is 0.9 μm;

[0107] Among them, the specific process of electromagnetic coupling enhancement treatment is:

[0108] After the cutting tool is cleaned by ultrasonic wave, it is loaded into the electromagnetic coupling treatment equipment, the electromagnetic field frequency is set to 2MHz, the magnetic field strength is set to 150mT, and then high-purity nitrogen is introduced, the gas flow rate is controlled at 60L / min, and then the temperature is gradually increased to 600℃ at a heating rate of 10℃ / min, so as to decompose the nitrogen into high-energy active nitrogen ions and form a TiN layer on the surface of the cutting tool;

[0109] The specific process of surface coating treatment is:

[0110] In an Ar atmosphere, the cutting tool was subjected to ion bombardment treatment with a substrate bias of -180 V for 20 min, and then high-purity Ar was introduced with a flow rate controlled at 40 sccm and a substrate bias of -170 V. The Cr and Al targets were started with sputtering powers of 140 W and 130 W, respectively, and the deposition time was 60 min to obtain a CrAlN layer.

[0111] Add high purity N 2 , Ar and N 2 The flow rates are 40sccm and 10sccm respectively, and the target material is adjusted to Cr 0.35 Al 0.45 Si 0.10 The alloy target material, the sputtering power is 150W, the substrate bias voltage is -100V, and the deposition time is 30min to obtain the CrAlSiN layer;

[0112] Then in Ar and N 2 High purity B is introduced into the atmosphere2 H 6 , gas flow rate is 100sccm, target material is Cr 0.30 Al 0.60 B 0.10 , the sputtering power is 150 W, the substrate bias is -100 V, and the deposition time is 30 min to obtain the CrAlBN layer.

[0113] Comparative Example 1

[0114] The titanium alloy cutting tool and processing method of this comparative example 1 are different from those of the embodiment 1 in that in step S1 , the binder phase contains only metal cobalt powder.

[0115] Comparative Example 2

[0116] The titanium alloy cutting tool and processing method of this comparative example 2 are different from those of the embodiment 1 in that: in step S1, the additive does not contain modified CeO 2 .

[0117] Comparative Example 3

[0118] The cutting tool and processing method of the titanium alloy material of the comparative example 3 are different from those of the embodiment 1 in that in step S4, there is no pressure sintering stage in the sintering method.

[0119] Comparative Example 4

[0120] The cutting tool and processing method of the titanium alloy material of Comparative Example 4 are different from those of Example 1 in that in step S6, the cutting tool is not subjected to electromagnetic coupling strengthening treatment.

[0121] Comparative Example 5

[0122] The cutting tool and processing method of the titanium alloy material of the comparative example 5 are different from those of the embodiment 1 in that in step S6, the surface coating treatment is not performed on the cutting tool.

[0123] The following experiments are conducted on the above-mentioned embodiments 1-2 and comparative examples 1-5 to verify or understand their performance. In the cutting tools of titanium alloy materials prepared in the above-mentioned embodiments 1-2 and comparative examples 1-6.

[0124]

[0125] Table 1 Comparison of cutting tool performance tests of titanium alloy materials in various embodiments and comparative examples

[0126] According to Table 1 above, in the titanium alloy cutting tools prepared in Example 1 and Example 2, titanium-based alloy powder is added to the binder phase, which enhances the high temperature strength and heat resistance of the cutting tools, avoids the problem of softening and failure of the binder phase during high temperature cutting, and gives the tools lightweight and high strength characteristics, thereby improving cutting efficiency. 2 The uniformity of the microstructure and the interface bonding strength of the material are improved, thereby improving the densification effect of sintering, making the tool free of stress concentration points, and significantly enhancing the crack resistance. In addition, CeO 2 The antioxidant effect can improve the wear resistance and service life of the tool; the introduction of the pressure sintering stage in the sintering process can effectively eliminate the micropores inside the material, significantly improve the density, mechanical strength and toughness of the material, optimize the microstructure, and make the tool show better heat resistance and fatigue resistance in high-temperature cutting; the electromagnetic coupling strengthening treatment can generate a dense TiN layer on the tool surface, greatly improving the surface hardness and wear resistance of the tool, while enhancing the antioxidant performance, resisting thermal fatigue and oxidative wear in high-temperature cutting; the multi-layer coating treatment deposits CrAlN, CrAlSiN and CrAlBN coatings layer by layer to form a gradient-optimized structure, taking into account hardness, wear resistance, toughness and high-temperature resistance, which not only reduces the friction coefficient, but also significantly improves the bonding strength between the coating and the substrate, avoiding the problem of coating peeling.

[0127] In Comparative Example 1, the binder phase contains only metal cobalt powder without the addition of titanium-based alloy powder, resulting in a significant decrease in the high-temperature strength and heat resistance of the cutting tool. The binder phase is easily softened and fails during high-temperature cutting. The lack of specific strength and lightweight characteristics of the titanium-based alloy leads to insufficient overall strength and rigidity of the tool, and the increased weight affects the cutting efficiency.

[0128] In Comparative Example 2, the additive does not contain modified CeO 2 , which will lead to uneven microstructure of cutting tool materials, weakened interface bonding, decreased sintering densification effect, and easy formation of stress concentration points inside the material, thereby reducing crack resistance; during high-temperature cutting, the softening of the bonding phase intensifies, resulting in decreased high-temperature strength and heat resistance of the material. Due to the lack of CeO 2 Due to the antioxidant effect, the surface of the cutting tool is prone to oxidation corrosion, and the wear resistance and service life are significantly reduced;

[0129] In Comparative Example 3, there is no pressure sintering stage in the sintering method, which will lead to insufficient densification of the cutting tool material, and micropores are likely to remain inside, thereby reducing the mechanical strength and toughness of the material, and also weakening the interface bonding force, resulting in uneven microstructure; during high-temperature cutting, the heat resistance and fatigue resistance of the material are reduced, and cracks are likely to expand or break, thereby shortening the tool life;

[0130] In Comparative Example 4, the cutting tool was not subjected to electromagnetic coupling strengthening treatment, and a dense TiN layer was not formed on the surface of the cutting tool, resulting in insufficient surface hardness and wear resistance, and reduced oxidation resistance. The tool was susceptible to oxidation and thermal fatigue during high-temperature cutting, and surface wear was aggravated.

[0131] In Comparative Example 5, the cutting tool was not subjected to surface coating treatment, and the surface of the cutting tool lacked the protection of multiple layers of coating, resulting in significantly reduced wear resistance and high temperature resistance. During the cutting process, the tool surface was in direct contact with the workpiece, the friction coefficient increased, and severe wear and built-up edge were prone to occur. The lack of coating also led to a weakening of antioxidant ability, and the tool surface was prone to oxidation corrosion in a high temperature environment, and the service life was greatly shortened.

[0132] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cutting tool processing method for titanium alloy material, characterized in that: The following steps are involved: S1. Prepare the raw materials according to the following weight percentages: Hard phase WC75%-80%; The bonding phase is composed of metal cobalt and titanium-based alloy powder, 10%-15%, wherein metal cobalt accounts for 50%-60% of the total bonding phase, and the titanium-based alloy powder accounts for 40%-50%. The chemical composition of the titanium-based alloy powder is: titanium 68%-75%, aluminum 15%-25%, and vanadium 4%-8%; Additives 5%-8%, the additives are composed of the following components: TiO2 2%-3%, TiB2 1%-2%, and modified CeO2 2%-3%; S2, putting the hard phase, the binder phase and the additive into a ball mill according to the raw material ratio for ball milling, and obtaining a mixed powder after spray drying; S3, pressing the mixed powder into a shape to obtain a tool blank; S4, sintering the tool blank by a segmented sintering method; S5, mechanically cutting the sintered tool blank to obtain a cutting tool; S6. Perform electromagnetic coupling strengthening treatment and surface coating treatment on the cutting tool in sequence to form a TiN layer, a CrAlN layer, a CrAlSiN layer and a CrAlBN layer on the surface of the cutting tool in sequence.

2. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: In step S6, the specific process of electromagnetic coupling enhancement processing is as follows: After the cutting tool is ultrasonically cleaned, it is loaded into the electromagnetic coupling processing equipment, the electromagnetic field frequency is set to 2MHz, the magnetic field strength is set to 150mT, and then high-purity nitrogen is introduced. The gas flow rate is controlled at 60-80L / min, and then the temperature is gradually increased to 600-800℃ at a heating rate of 10-15℃ / min, thereby decomposing the nitrogen into high-energy active nitrogen ions and forming a TiN layer on the surface of the cutting tool.

3. The cutting tool processing method of titanium alloy material according to claim 2, characterized in that: In step S6, the specific process of surface coating treatment is as follows: In an Ar atmosphere, the cutting tool is subjected to ion bombardment treatment with a substrate bias voltage of -180V for 10-20min, and then high-purity Ar is introduced with a flow rate controlled at 40-50sccm, and a substrate bias voltage of -170V is applied. The Cr and Al targets are started with sputtering powers of 140W and 130W, respectively, and the deposition time is 60min to obtain a CrAlN layer. High-purity N2 was added to the Ar gas, with the flow rates of Ar and N2 being 40sccm and 10sccm respectively, and the target material was adjusted to Cr 0.35 Al 0.45 Si 0.10 The alloy target material, the sputtering power is 150W, the substrate bias voltage is -100V, and the deposition time is 30min to obtain the CrAlSiN layer; Then, high-purity B2H6 was introduced into the Ar and N2 atmosphere with a gas flow rate of 10-20sccm and the target material was Cr 0.30 Al 0.60 B 0.10 , the sputtering power is 150 W, the substrate bias is -100 V, and the deposition time is 30 min to obtain the CrAlBN layer.

4. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: The modification process of the modified CeO2 is as follows: Place CeO2 particles with a particle size of 100-200 nm in an ultrasonic cleaning device, add a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:1, wash for 10-15 minutes, then filter with filter paper to take out the CeO2 particles, and then place the CeO2 particles in an oven at 60-80°C and dry for 3-5 hours to ensure that there is no residual liquid on the surface of the CeO2 particles; Subsequently, the CeO2 particles are placed in a vacuum plasma treatment device, and the cavity of the vacuum plasma treatment device is evacuated to a vacuum degree below 0.001Pa. Then, high-purity Ar is introduced into the cavity to maintain the pressure in the cavity at 20-50Pa. The radio frequency plasma source is started with a frequency of 13.56MHz and a power of 200-400W, so that the CeO2 particles are evenly bombarded in the plasma environment. The treatment time is 3-5min.

5. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: The thickness of the TiN layer is 1-4 μm.

6. The cutting tool processing method of titanium alloy material according to claim 5, characterized in that: The thickness of the CrAlN layer is 0.5-0.7 μm, the thickness of the CrAlSiN layer is 0.6-0.8 μm, and the thickness of the CrAlBN layer is 0.7-0.9 μm.

7. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: In step S2, ethanol is added as a ball milling medium during the ball milling of the raw material, and 0.5 wt % of polyethylene glycol is added as a molding agent for ball milling. The ball-to-powder ratio is 10:1, and the ball milling time is 12-24 hours.

8. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: In step S3, the mixed powder is first preliminarily pressed by cold isostatic pressing equipment at a pressing pressure of 200-300 MPa, and then the preliminarily pressed tool blank is placed in a hot isostatic pressing equipment for high-temperature compaction treatment, with the temperature controlled at 900-1100°C, the pressure at 50-100 MPa, and the insulation time at 1-2 hours.

9. The cutting tool processing method of titanium alloy material according to claim 1, characterized in that: In step S4, the method of segmented sintering is specifically as follows: S41, dewaxing stage: after evacuating the sintering furnace to 20-50Pa, hydrogen is introduced, and the furnace temperature is increased to 350-400°C at a heating rate of 35-45°C / min, and kept at this temperature for 4-6h; S42, vacuum sintering stage: the furnace temperature is raised to 1250°C at a heating rate of 20-25°C / min, and kept at this temperature for 50-60min, and then the furnace temperature is raised to 1350°C at a heating rate of 8-10°C / min, and kept at this temperature for 70-90min; S43, pressure sintering stage: after vacuum sintering is completed, argon gas is introduced into the furnace to increase the pressure in the furnace to 50-100 mbar, and at the same time, the furnace temperature is increased to 1450-1500°C at a heating rate of 5°C / min and maintained for 30-60 minutes; S44, cooling stage: after stopping heating, the furnace temperature is lowered to 1000°C at a cooling rate of 12-25°C / min, 950-980mbar argon is introduced at this temperature for forced cooling, and the cooling rate is controlled at 10-15°C / min until the furnace temperature is lower than 100°C, and the tool blank is taken out.

10. A cutting tool for titanium alloy material, characterized in that: The titanium alloy cutting tool is prepared by the titanium alloy cutting tool processing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for in-situ integrated preparation of Ti (C, N)-based metal ceramic cutter material with high heat resistance

    CN112743080A

  • Gradient hard alloy cutter with high-entropy alloy binding phase and preparation method of gradient hard alloy cutter

    CN118893212A

  • Selectively leached thermally stable cutting element in earth-boring tools, earth-boring tools having selectively leached cutting elements, and related methods

    US20230129943A1

  • Diamond coating cutting tool

    US20240300027A1

Cited By

  • Preparation method of high-toughness hard alloy with bionic laminated structure and cutting tool

    CN121571659A

  • A method for preparing a high strength and toughness hard metal with a biomimetic laminated structure and a cutting tool

    CN121571659B